A comunicação suplementar e/ou alternativa na vida de pessoas com paralisia cerebral, adultas e institucionalizadas - Silva, Marisa Cláudia Feital da (2007)
The aim of this work, was to verify how the AAC can affect the life of two adults with a non articulated speech, due to the cerebral palsy, on both, considering the fact that they are living as internals in an Institution. It was chosen as method the case study with observation evolved by a six months period of time. It has been made reports and pictures (movies) during the sessions of speech therapy, with the two patients. Along with the sessions, it was made by the therapist and the two patients, low technology boards using P.C.S. (Picture Communication Symbols). During that same period of time, the therapist too has been included as an observer in the institute routine, on the purpose to acquire data, about the overall environment. It was followed and reported the effect over the lives of the two patients due to the interaction, provided by the P.C.S. system application, from the point of view of their subjectivities, and daily routine of life. Therefore as a result the data showed that from the beginning of the use of low technology boards construction process, the two patients have developed conditions that contributed for their autonomy with regards to their people. Their new behavior were noticed inside the institution and an unfamiliar feeling was observed. By the analysis of the data acquired, the Institution people arrived to the conclusion that the work was good for the patient s subjectivities, with an overall positive effect on their behavior. So they started to be noticed and respected in the Institution